Condom use among students': the influence of condom self- efficacy, social norms and affective attitude towards condom (2008)
The study examined the influence of condom self-efficacy, social norms and affective altitude towards condom on reported condom use among university students. A total of 183 students participated in the study. Their age ranged between 15 and 32 years (Mean = 24, SD= 2.8). One hundred and fifty-one were single while 32 were married. The study revealed that condom self-efficacy, social norms and affective attitude towards condom play a significant role in reported use among university students. The implications of the findings on student sexual behaviour and condom use were discussed